Assessment of Toxoplasma immunoglobulins, α-fetoprotein, and dopamine sera levels: insights into heroin addicts’ characteristics - Somaya H. Shaheen; Enas A. El Saftawy; Basma E. Aboulhoda; Mona M. Abdulwehab; Asmaa Ibrahim; Marwa M. Zein; Mohamed F. Farag; Nagwan M. Salama; Heba M. Elwi; Naglaa SH. Elkholy; Mansour Abdullah Alghamdi; Mennat-Allah Tarek (BMC Psychiatry)
Abstract Background Heroin’s systemic effects relative to addicts’ characteristics have not been fully investigated. The frequencies of dopamine and α-fetoprotein and the coincidence of toxoplasmosis were assessed. Method The study involved 49 drug addicts and 48 healthy controls. Personal history was taken. Anti-Toxoplasma IgG and IgM, dopamine, and α-fetoprotein in serum were measured using ELISA. Results Overall, 59.2% were ˃ 30 -years- old, 91.8% were low-educated, 85.7% had craftwork, 28.6% had a positive family history, and 49.0% used the intravenous route. Compared to healthy controls, a higher prevalence of Toxoplasma Ig G, significant dopamine reduction, and relatively increased α-fetoprotein were observed. Positive Toxoplasma Ig M serum levels were not recorded, and only 2 patients had equivocal levels. Among addicts, Toxoplasma-IgG levels were equivocal and positive in 18- to 30-year-olds and low-educated, equivocal in craftworkers (33.3%), positive in mental work (28.6%), with insignificant frequencies of relapses. Smoking duration and heroin consumption, all administration routes, and positive family history had relatively higher frequencies of negative anti-Toxoplasma IgG. Higher frequencies of abnormal α-fetoprotein were present in above-thirties addicts, craftwork, number of relapses, the number of cigarettes, early onset, longer duration, amount of heroin, positive family history, and combined routes of administration. Frequencies of decreased dopamine were in above-thirties addicts, graduates, craftworkers, lower relapses, and increased cigarette and substance use. Toxoplasma IgG and Ig M serum levels are inversely correlated with the respective duration and onset of smoking. The number of cigarettes positively correlated with α-fetoprotein. Dopamine correlated inversely with α-fetoprotein. Conclusion Higher past exposure to T. gondii was observed among drug addicts, which tended to be chronic latent, not active disease. Toxoplasmosis and altered dopamine and α-fetoprotein serum levels are potentially affected by age, social status, and cigarette consumption. Dopamine and α-fetoprotein alterations are coincident with increased heroin use.